Legal Protection for Victims of Sexual Violence Under Indonesian Positive Law - Danial Syah; Faradila Putri; Rifky Hafiz Suryana; Muhammad Iqbal Siregar; Widiya Anjelina Simamora; Patrik Andreson Lumban Gaol (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Sexual violence is a violation of human rights that significantly affects the physical, psychological, and social well-being of victims. Although Indonesia has established several legal frameworks to protect victims—including Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS)—its implementation continues to face various challenges. This study aims to analyze the forms of legal protection provided to victims of sexual violence under Indonesian positive law and to identify obstacles in its enforcement. The research employs a descriptive qualitative method using a literature review of primary, secondary, and tertiary legal sources. The findings indicate that the TPKS Law offers substantial progress by strengthening victims' rights to handling, protection, and recovery in a comprehensive manner. Nevertheless, its effectiveness remains hindered by the limited capacity of law enforcement officers to apply trauma-informed approaches, inadequate victim support services, persistent societal stigma, and weak interinstitutional coordination. This study concludes that enhancing the implementation of the TPKS Law requires improving law enforcement competence, expanding integrated victim services, and increasing public awareness to ensure that legal protection for victims is carried out effectively and equitably.